2018
DOI: 10.3390/su10103572
|View full text |Cite
|
Sign up to set email alerts
|

Elephant Crop Damage: Subsistence Farmers’ Social Vulnerability, Livelihood Sustainability and Elephant Conservation

Abstract: African elephants (Loxodonta africana) induce considerable crop damage risks, shocks and stresses on subsistence farmers at the wildlife-agriculture interface. In this study, we explored the social dimensions of human-elephant interactions in the wildlife-agrarian landscape. The study aimed at unraveling the associated hazardous conditions and nature of the subsistence farmers’ social vulnerability and practices with respect to elephant crop damage, subsistence farmers’ livelihoods, and elephant conservation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 90 publications
2
11
0
Order By: Relevance
“…Furthermore, several studies (including the current study) have performed content analysis for questionnaires, interviews, and essay responses. However, previous studies have focused on tourism [43], the perceptions of farmers on wildlife management [44], and the risks of living with wildlife [45][46][47], but no study has utilized text-based questionnaires to assess individual perceptions of wildlife.…”
Section: Methodologies Utilized In Previous Researchmentioning
confidence: 99%
“…Furthermore, several studies (including the current study) have performed content analysis for questionnaires, interviews, and essay responses. However, previous studies have focused on tourism [43], the perceptions of farmers on wildlife management [44], and the risks of living with wildlife [45][46][47], but no study has utilized text-based questionnaires to assess individual perceptions of wildlife.…”
Section: Methodologies Utilized In Previous Researchmentioning
confidence: 99%
“…With the deepening of research on livelihood issues conducted by relevant scholars, the sustainable livelihood approach (SLA) has gradually developed in theory and practice [7][8][9][10], and the framework for sustainable livelihood analysis proposed by the U.K.'s Department for International Development (DFID) is the most typical. This framework consists of five parts: vulnerability background, livelihood capital, organizational structure and policy system, livelihood strategy, and livelihood status; additionally, it regards rural households as the activity subjects in the vulnerability background and reflects the rural households' livelihoods from the aspects of livelihood capital, livelihood strategies, and livelihood status [2,11]. Specifically, livelihood capital represents the elements that enhance people's capacity to engage in different livelihood activities, and it not only plays a major role in making a living but also offers people the opportunity to influence the institutions and structures within which they operate [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Kato et al [ 24 ] even stated that, in this context, human–human conflict is ironically an even more complicated problem than human–wildlife conflict. This is an unfavorable situation that should be avoided as it makes it very difficult to forge stakeholder agreement in management plans, as has been noted by many authors [ 24 , 36 , 55 , 56 , 60 , 61 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our study indicated that they are the result of the perceived risk of forest use limitations and the damage caused by these animals ( Table 1 ), which becomes more important when it is happens directly to one’s own property ( Figure 4 ). These are typical reasons that shape society’s attitude towards the presence of wild animals [ 25 , 36 , 41 , 43 , 62 , 63 , 64 , 65 ]. In the study by Klich et al [ 18 ], it was suggested that if the European bison does not occur in a given area, perception of this species is likely to be shaped by other wild species; on the other hand, where the European bison is present, its management is of primary importance.…”
Section: Discussionmentioning
confidence: 99%